Integração mássica e energética em sistemas de oxicombustão na indústria de alimentos - Severo, Ihana de Aguiar (2020)
The development of alternative technologies aimed at mitigating carbon dioxide has been the target of several scientific pieces of research, highlighting the sustainability and economy of industrial production processes. Carbon capture through oxy-combustion is considered a potential approach to meet these requirements; however, it has some limitations due to the demand for oxygen and energy, which can be overcome with the microalgal photobioreactors integration. The process integration proposes to improve the thermal efficiency of combustion systems, reducing costs and harmful emissions, through the technique of biological carbon capture and utilization. In this sense, the objective of the present work was to develop an oxy-combustion system through mass and energy integration. First, the study focused on building a laboratory-scale furnace, evaluating the thermal performance parameters, as well as evaluating the kinetic parameters, the photosynthetic quotient, and the photobioreactor exhaust gases. Subsequently, the life cycle assessment and the bioeconomy of the integrated process was carried out and, in the end, a study on the technological prospecting of patents. The results obtained showed that through the enrichment of the photobioreactor exhaust gases, a gain in the system's thermal efficiency was obtained. Simultaneously, potential improvements in environmental performance were evidenced concerning sustainability metrics and reduction in utility costs, including fuel and oxidizer consumption. The process also met the requirements for innovation and inventiveness, demonstrating the potential for technology transfer to the industrial sector.